Do Indigenous patients in Australia's Northern Territory present with more advanced colorectal cancer? A cohort study based on registry data. Issue 10 (28th August 2019) - Read, David J.; Hayes, Ian
Abstract : Background: Previous studies show that Indigenous Australians (IndA) of the Northern Territory (NT) present later and have lower survival for colorectal cancer (CRC) compared with non‐Indigenous (NI) Territorians. This study compared the odds of presenting with advanced‐stage CRC between IndA and NI adjusted for demographic, histopathological and surgical features. Methods: A cohort study of NT Cancer Registry (NTCR) CRC cases from 2005 to 2014. All (667) persons notified to the NTCR with a new diagnosis of CRC were included, of which 504 had sufficient data for analysis. The NTCR was used for case identification and linked to available hospital clinical data. The principal exposure was IndA compared with NI and the principal outcome was odds of presenting with advanced‐stage tumour (III and IV) compared with early‐stage (I and II). Univariable and multivariable logistic regression were performed on all relevant variables. Results: Univariable logistic regression found no difference in the odds of advanced CRC between IndA and NI (odds ratio (OR) 0.99, 95% confidence interval (CI) 0.56–1.76, P = 0.982). This effect remained insignificant adjusted for the effects of sex, tumour position, remoteness and time period (OR 0.85, 95% CI 0.47–1.55, P = 0.606) and when adjusted for tumour grade, lympho‐vascular invasion, lymph node harvest and emergency status (OR 1.39, 95% CI 0.64–3.03, P = 0.401). Conclusions: In distinction from previous studies, there was no evidence that IndA of the NT presented with later stage CRC in 2005–2014. Other factors (incomplete treatment or comorbidity) may be responsible for the continued observed survival disparity. Abstract : Previous studies have shown that Indigenous Australians in the Northern Territory have allowed survival from, and present at a later stage with colorectal cancer than non‐Indigenous Australians. This study shows that a later stage of presentation is no longer present, implying that other factors such as treatment complaint or comorbidity may be responsible for the continued survival disparity.